High Recurrence Rate of Myxofibrosarcoma: The Effect of Radiotherapy Is Not Clear. (1st October 2019) - Teurneau, Hjalmar; Engellau, Jacob; Ghanei, Iman; Vult von Steyern, Fredrik; Styring, Emelie
Abstract : Background . Myxofibrosarcoma (MFS) is one of the more common types of soft-tissue sarcoma (STS) in patients over 60 years of age. Local recurrence (LR) rates have been reported to be higher compared to other STS types. Patients and Methods . Using a population-based series from the southern Sweden health care region, 56 consecutive patients with MFS and localized disease at diagnosis were analyzed with respect to LR and distant metastases after surgery ± adjuvant treatment. Results . The overall local recurrence ( n = 15) and metastasis ( n = 13) rates were 27% and 21%, respectively; 6 patients had both. Surgical margin was the only statistically significant prognostic factor for LR. Patients operated with a marginal margin had an HR of 4.5 (CI 1.3–15.1, p = 0.02 ) and those operated with an intralesional margin 9.4 (CI 2.0–43.5, p = 0.004 ) compared to those operated with a wide surgical margin. There was no difference in the LR rate depending on radiotherapy or not, although the latter group had smaller and more superficial tumors. 23 patients received radiotherapy, 9 of whom developed LR, all within the irradiated field. A tumor size >5 cm and intralesional surgical margin were shown to be risk factors for distant metastases. Conclusions . The rate of LR for patients with myxofibrosarcoma was high. The impact of RT on local tumor control was unclear. The surgical margin was important for both local and distant tumor control. Large tumor size was a risk factor for distant metastasis.